8(2n+3)=7(8n+8)+9

Simple and best practice solution for 8(2n+3)=7(8n+8)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(2n+3)=7(8n+8)+9 equation:



8(2n+3)=7(8n+8)+9
We move all terms to the left:
8(2n+3)-(7(8n+8)+9)=0
We multiply parentheses
16n-(7(8n+8)+9)+24=0
We calculate terms in parentheses: -(7(8n+8)+9), so:
7(8n+8)+9
We multiply parentheses
56n+56+9
We add all the numbers together, and all the variables
56n+65
Back to the equation:
-(56n+65)
We get rid of parentheses
16n-56n-65+24=0
We add all the numbers together, and all the variables
-40n-41=0
We move all terms containing n to the left, all other terms to the right
-40n=41
n=41/-40
n=-1+1/40

See similar equations:

| 8x-9=-3x+5 | | -1=3y-5 | | 4t-36=0 | | p=318 | | 10+5x/15=4 | | 4/5x+4=-2/3 | | 1.3z+1,5=5.4 | | 15=1.05^x | | 2x−7=  −3x+18 | | 2x−7=  −3x+18−3x+18 | | 8=¾c+12-C+4 | | 3¡2x¡(x+4)=¡11 | | x^2-7x-1=14-9x | | 3(x+10)+2(x+15)=-15 | | 8-16c=4c+28 | | 7(x-10)=5(x+10) | | -5f-5=-60 | | 10+6b=40 | | 2=n^2+5n+6 | | 4(5x+68)=3(x+68) | | 2x=5(-3x-10)=-154 | | 4f-6=38 | | 2x+7=2x=7 | | 3e+6=33 | | -12=2/3x+2 | | 30+2e=48 | | 10(x+3)-(x-4)=x5+3 | | 4x+3(5x-3)=29 | | X-2(x+2)=4 | | 33=25+3x | | 2c+5=c+83 | | -4x+7=10+37x |

Equations solver categories